E-Application and Dss for Farmers to Sell Food Crops Through E-Auction - M, Dharmateja; Kothuri, Sriraman; Venkateswararao, Kuna. (International Journal of Engineering and Technology, 2018)
Farmers have been facing issues while selling their food crops in market due to intermediate persons, who actually got profit by setting low price while buying from farmers and later sell the same at higher price to the customers. Through e-application is developed for farmers to set their own price to their products and allows buyers for e-auction. Farmers can set the initial bid amount based on quality, life time and current market price of the products before going for e-auction. The buyers can find nearest sellers through GPS navigation system. Choices locked once validity of bidding over and corresponding buyer, seller get notified through SMS. The interface also act as Decision Support System(DSS) for farmers to post their queries for getting advice's from agriculture specialists.Â
Keywords: GPS; E-AUCTION; DSS; SMS